2022
DOI: 10.3390/jcm12010099
|View full text |Cite
|
Sign up to set email alerts
|

The Prescription Pattern of Heart Failure Medications in Reduced, Mildly Reduced, and Preserved Ejection Fractions

Abstract: A substantial proportion of patients with heart failure (HF) receive suboptimal guideline-recommended therapy. We aimed to identify the factors leading to suboptimal drug prescription in HF and according to HF phenotypes. This retrospective, single-centre observational cohort study included 702 patients admitted for worsening HF (HF with a reduced ejection fraction [HFrEF], n = 198; HF with a mildly reduced EF [HFmrEF], n = 122; and HF with a preserved EF [HFpEF], n = 382). A score based on the prescription an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…in those patients ( 13 , 28 ). This is supported by recent observational and clinical trial data indicating their broad uptake in patients discharged with HFmrEF/HFpEF ( 29 , 30 ). In the present study, prescription rates of beta-blockers and MRA at discharge in patients with HFmrEF/HFpEF were lower (29.8% and 34.0%, respectively) compared with patients without pneumonia (49.4% and 45.8%, respectively) and the development of pneumonia was independently associated with a lower likelihood of providing beta-blockers and MRA at discharge in patients with HFmrEF/HFpEF.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…in those patients ( 13 , 28 ). This is supported by recent observational and clinical trial data indicating their broad uptake in patients discharged with HFmrEF/HFpEF ( 29 , 30 ). In the present study, prescription rates of beta-blockers and MRA at discharge in patients with HFmrEF/HFpEF were lower (29.8% and 34.0%, respectively) compared with patients without pneumonia (49.4% and 45.8%, respectively) and the development of pneumonia was independently associated with a lower likelihood of providing beta-blockers and MRA at discharge in patients with HFmrEF/HFpEF.…”
Section: Discussionsupporting
confidence: 64%
“…There was no difference in the prescription of ACEI/ARB/ARNI and SGLT2I. Overall prescription of SGLT2I in patients with HFmrEF/ HFpEF was higher than in some of the contemporary studies (29,30). This may reflect the high prevalence of concomitant T2DM, but also greater confidence among the treating physicians regarding the safety of SGLT2I initiation early after stabilisation in AHF.…”
Section: Discussionmentioning
confidence: 72%
“…A recent study performed in Spain and including patients with HFpEF up to 2019 found that 79.8% were taking RAAS inhibitors (12% sacubitril–valsartan), 65.9% were taking betablockers, 27.7% mineralocorticoid receptor antagonists and only 5.1% SGLT2i [ 1 ]. A study performed in France showed that 73.7% were taking RAAS inhibitors, 80.3% were taking betablockers, and 21.6% mineralocorticoid receptor antagonists [ 22 ]. Despite having improved the percentage of patients taking treatment recommended for HF compared with previous studies, there is still considerable room for improvement in the form of a more favorable prognosis and reduced risk of readmission with HF, especially when treatment is started early, including both before and after discharge, which is the most vulnerable period for affected patients [ 6 , 23–25 ].…”
Section: Discussionmentioning
confidence: 99%
“…), female sex, lower body habitus/body mass index (BMI), HR, SBP and serum potassium level. 18,26,47,[62][63][64][65][66] These parameters may be perceived as an individual's fragility, leading to either careful up-titration of GDMT or no intent at all. 25 Indeed, there was an independent association between obesity (BMI ≥30 kg/m 2 ) and likelihood of prescription/ up-titration to target doses of GDMT in the Swedish Heart Failure Registry.…”
Section: Factors Associated With Suboptimal Treatment: Potential Caus...mentioning
confidence: 99%